2018
DOI: 10.1098/rsos.180225
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis-like respiratory infection in 245-million-year-old marine reptile suggested by bone pathologies

Abstract: An absence of ancient archaeological and palaeontological evidence of pneumonia contrasts with its recognition in the more recent archaeological record. We document an apparent infection-mediated periosteal reaction affecting the dorsal ribs in a Middle Triassic eosauropterygian historically referred to as ‘Proneusticosaurus’ silesiacus. High-resolution X-ray microtomography and histological studies of the pathologically altered ribs revealed the presence of a continuous solid periosteal reaction with multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…[27,43,44]), have been generally anecdotal in nature, reporting only the description of a specific pathology in one or two specimens (e.g. [45]) or suite of pathologies in a single specimen (e.g. [46]).…”
Section: Discussionmentioning
confidence: 99%
“…[27,43,44]), have been generally anecdotal in nature, reporting only the description of a specific pathology in one or two specimens (e.g. [45]) or suite of pathologies in a single specimen (e.g. [46]).…”
Section: Discussionmentioning
confidence: 99%
“…Identification can be especially problematic when a lesion lacks features consistent with a single disorder, or conversely, expresses features that are present in several conditions. The lack of precise identification means that several of these lesions can only tentatively be identified as “-like” (such as the “tuberculosis-like” bony pathologies reported in Surmik et al 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Today, respiratory diseases of archosaurs include inflammatory, infectious (bacterial, viral, fungal, mycobacterial, parasitic), and neoplastic etiologies 36 , 37 . A mycobacterial-like infection in a 245-million-year-old marine reptile 38 is the oldest described. This specimen exhibits parosteal proliferation on dorsal ribs with histology that reveals tissue changes similar to modern cases of mycobacterial pulmonary infection.…”
Section: Introductionmentioning
confidence: 99%
“…Surmik et al (): Figs. 2 and 3) thin sectioned the proximal part of a pachyostotic dorsal rib from the Anisian of Poland that probably belongs to a pistosauroid.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation of the development of the spongiosa in the medullary region with size as Canoville et al (2016) found was not documented for Triassic Sauropterygia. Surmik et al (2018): Figs. 2 and 3) thin sectioned the proximal part of a pachyostotic dorsal rib from the Anisian of Poland that probably belongs to a pistosauroid.…”
Section: Comparison With Other Tetrapod Vertebrae and Ribsmentioning
confidence: 99%